Remnant Movement. - Grewendorf, Günther (Studies in Generative Grammar SGG., 2015)
This book addresses two crucial problems associated with the phenomenon of Remnant Movement: First, what evidence can be brought to bear in favor or, or opposing to Remnant Movement analyses of linguistic phenomena? Secondly, what does the presence or absence of Remnant Movement in the syntax tell us about constraints imposed by Universal Grammar on syntactic operations?